User perception of trust in interface design for electronic commerce (E-Commerce) / Nur Liyana Abdul Malik - Abdul Malik, Nur Liyana (2009)
Adoption and usage of Electronic Commerce (E-Commerce) websites is found to be particularly effected by trust concerns by the consumers. The lack of trust mostly due to security and privacy concerns, unfamiliar online services, lack of direct interaction with product and sellers, as well as poor credibility of online information. This research is aim to know what the consumer trust perception is when they engage with the B2C ECommerce transaction. The study is seen important, as it identified user's interface requirements for trust elements toward the B2C E-Commerce website. These identification processes has led to the creation of a proposed user's interface design based on Model of Trust in E-Commerce (MoTEC) that provides a framework making explicit factor likely to affect the customer trust. There are four dimensions in the MoTEC model which is pre-interactional filters, interface properties, informational content and also relationship management. This research focuses only on the preinteractional filters and interface properties in MoTEC. This study has specified its scope to the people in Shah Alam, Selangor, also at Sintok, Kedah and related organization, besides focusing on B2C E-Commerce website from the aspect of trust. The interface design is the main outcome, of this research, excluding the content of the rest of the B2C E-Commerce website. Besides benefiting the customers that would like to engage in the B2C E-Commerce, it indirectly benefits the B2C E-Commerce web developer, by exposing them toward the interface design that will promote customer trust. In sum, many parties can gain many benefit through the B2C E-Commerce website. Interface requirements and trust elements were obtained though research questionnaire, while the design of the B2C E-Commerce website was created by using Joomla 1.5.2 Extension with Virtuemart 1.1.3. The result obtained was analyzed and led to the design working prototype to show how the interface in B2C E-Commerce website can affect the consumer perceptions toward the trust development in B2C E-Commerce.